Tax evasion and risky investments in an intertemporal context: An experimental study - Sebastian Giese; Antje Hoffmann (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
In this experimental study of tax evasion and its determinants participants earn their income in a complex stochastic intertemporal environment including the possibility to invest into a risky asset. The earned income has to be declared in four tax returns which are randomly verified. If tax evasion is detected, penalty depends on evaded taxes. Twice the tax revenue is donated to charity organizations. Our main results show that higher income induces tax fraud and that gender differences exist.
urn:nbn:de:kobv:11-10047361
Keywords: 330